Education Sectoral and OR+ (Thematic) Report January – December 2018 - UNICEF Jamaica (UNICEF Jamaica, 2019)
This report notes that in 2018, all UNICEF-supported interventions under the Lifelong Learning programme component focused on equity in education and revolved around the child-friendly school ethos, providing support to disadvantaged children with an emphasis on those living in rural areas and those with special needs. Along these lines, UNICEF supported the implementation of innovative scalable pilot projects aiming at promoting a child-friendly school model through a focus on reducing school violence, ensuring safe journeys to and from schools and promoting inclusive, child-centred, game-based teaching approaches. UNICEF also contributed to significant policy and programmatic changes to increase access to early childhood education for children zero to three years old and children with disabilities. In 2018, UNICEF positively impacted the lives of close to 50,000 children through school and community-based interventions aimed at increasing child-friendly school components such as eradicating school violence through the expansion of the School-wide Positive Behavioural Intervention and Support (SWPBIS) framework, promoting inclusive child-centered sports for development and student support approaches though the EduSport programme and strategically increasing support for inclusion at the early childhood level. The report also examines strategic context of the Jamaican education sector in 2018, results of theory of change output 3, constraints/lessons learned/good practices, financial analysis, and a future work plan.